Evolution of non-thyroidal illness syndrome in acute decompensation of liver cirrhosis and acute-on-chronic liver failure - Langer, Mona-May; Bauschen, Alina; Guckenbiehl, Sabrina; Klauss, Sarah; Lutz, Teresa; Denk, Gerald; Zwanziger, Denise; Moeller, Lars C.; Lange, Christian M. (Frontiers in Endocrinology, 2023)
Background and Aims: Non-thyroidal illness syndrome (NTIS) is frequent in critically ill patients and associated with adverse outcomes. We aimed to characterize the evolution of NTIS in patients with acute decompensation (AD) of cirrhosis and acute-on-chronic liver failure (ACLF), since NTIS is not well described in these newly defined syndromes. Methods: Thyroid hormones (TH) were quantified at baseline in consecutive patients with cirrhosis. In addition, 76 inflammatory mediators were quantified by proximity extension analysis assay in a subgroup of patients. Associations between TH, cirrhosis stage, mortality and inflammation were assessed. Results: Overall, 437 patients were included, of whom 165 (37.8%), 211 (48.3%), and 61 (14%) had compensated cirrhosis (CC), AD, and ACLF. FT3 concentrations were lower in AD versus CC, and further decreased in ACLF. Importantly, NTIS was present in 83 (39.3%) patients with AD and in 44 (72.1%) patients with ACLF (P<0.001). Yet, TSH and TSH-based indexes (TSH/FT3-ratio, thyroid index) showed an U-shaped evolution during progression of cirrhosis, suggesting a partially preserved responsiveness of the hypothalamus and pituitary in AD. Infections were associated with lower FT3 concentrations in AD, but not in ACLF. Low FT3 concentrations correlated significantly with 90-day mortality. Both, AD / ACLF and NTIS, were associated with signatures of inflammatory mediators, which were partially non-overlapping. Conclusion: NTIS is frequent already in AD and therefore precedes critically illness in a subgroup of patients with decompensated cirrhosis. This might constitute a new paradigm of TH signaling in cirrhosis, offering opportunities to explore preventive effects of TH in AD.